Stratégies argumentatives dans les discours politiques américains sur la législation des substances psychoactives : quel emploi du pathos à l’ère de la post-vérité ? - Sarah Bourse (Anglophonia)
The term “post-truth” was declared word of the year in 2016 by The Oxford Dictionary due to its relevance in the contemporary English-speaking world. Even though this word initially relates to lies at the core of political scandals (Iran-Contra scandal, Persian Gulf war), it recently has taken on another meaning, referring to a situation where objective facts have less impact than appeals to emotion and personal belief to influence public opinion (https://en.oxforddictionaries.com/word-of-the-year/word-of-the-year-2016).In this post-truth era where emotions take center stage the study of pathos in political discourse has never been more relevant. To what extent can this prevalence of emotions be observed in recent political speeches?The present study focuses on a corpus of political speeches about drug reform. The “War on Drugs” is a significant matter of public health that can be tackled from a medical or a criminal point of view. Given the diversity of opinions on this issue, it gives rise to many contradictory statements that are worth analyzing.